قيمة الوقت وتنظيمه لدى علماء الفكر التربوي الإسلامي من القرن الأول وحتى القرن الثامن الهجري - حسن، مرضية الزين مختار محمد (جامعة تعز فرع التربة - دائرة الدراسات العليا والبحث العلمي, 2022)
هدفت الدراسة للتعرف على قيمة الوقت وتنظيمه عبر القرون لدى عينة من علماء الفكر التربوي الإسلامي، في السنة النبوية الشريفة، والصحابة رضوان الله عليهم، والتابعين وتابع التابعين؛ وتوصلت الدراسة لعدة أهمها؛ أولى النبي صلى الله عليه وسلم الوقت عناية فائقة، فهو نعمة من الله تعالى وهبها للإنسان، ليصرفها فيما يعود عليه بالنفع والخير الوفير، بقوله صلى الله عليه وسلم (إن الصحة والفراغ نعمتان من نعم الله)، وردت الكثير من الأحاديث التي تدل على شرف الزمان وعلو منزلته، ويؤكد القرآن الكريم والسنة الشريفة، على أداء الشعائر الدينية في أوقاتها، (إن الصلاة كانت على المؤمنين كتابا موقوتا)، أن الصحابة رضوان الله عليهم كانوا أشد الناس حرصا على صرف أوقاتهم في عبادة الله ورضاه، وأكثر استفادة وتوظيفا للوقت، ورحم الله أبو بكر رضي الله عنه كان يعبد الله كأنه يراه ويحرص على وقته أكثر من أي شيء آخر، وكان ينصح الأمة باغتنام فرصة العمر قبل أن ينصرم الأجل، وأن يجعل المسلم وقته مشغولا على الدوام بعبادة الله، والقيام بأمره المسارعة إلى الاستزادة من العمل الصالح، ومن التابعين كان أويس القرني قيمة الوقت، وسرعة انقضائه، وأن ما مضى منه لا يعود، ومن رؤوس التابعين، وفضلائهم الحسن البصري؛ يقول في أهمية الوقت عند صحابة رسول الله صلى الله عليه سلم (أدركت أقواما كانوا على أوقاتهم أشد منكم حرصا على دراهمكم ودنانيركم)، ويقدم نصائح للغافلين، ويحذرهم من الركون إلى الأمل ويوصيهم باغتنام وقت اليوم الحاضر الذي يعيشونه. This study aims to investigate the time’s value and its management among the Islamic Educational Scholars through the centuries, within the noble prophetic Sunna, the companions of the Prophet (PBUH), and the followers of the followers of the prophet's companions. The main findings of the study are; the prophet Mohammed (PBUH) has paid great attention to time since it is a precious gift from Allah to the mankind, to be utilized positively. This is proved by the prophet Mohammed's hadith: ("There are two blessings in which many people incur loss: health and free time”). There were many hadiths which mention the value of time and its importance. The Holly Quran and Sunna emphasize the performance of the religious worship in its time: (For such prayers are enjoined on believers at stated times. Surah an Nisaa 103). Companions of the Prophet Mohammed (PBUH) were the most people who valued time and utilized it in worship. Abu Bakr- may Allah shower him with mercy and be pleased with him- used to worship Allah as if he saw him and was keen on his time more than anything else. He used to encourage people to use their time effectively before death comes. From the followers there was Oais al-Gurani who knows the value of time and how fast it may end and never return. Among the seniors of the followers was al-Hassan al-Bissry, who reported the value of time for the companions of the prophet Mohammed (PBUH) (I witnessed peoples who were concerned with time more than money). He also used to provide advice to the oblivious people and warns them to depend on hope, and advises them to seize time and use it effectively.
Keywords: القيم التربوية -- السنة النبوية -- التربية الإسلامية -- التفكير الابتكاري